Analisa Model Rapid Application Development Dalam Membangun Sistem Informasi Sekolah Mengemudi - Vivi Rahmawati; Susy Rosyida (Paradigma, 2020)
Technological developments, especially in the automotive sector, make automotive companies competing to produce vehicles or means of transportation that are in accordance with the demands of society at this time. The public wants a means of transportation that is safe, comfortable, environmentally friendly and economical. To drive a private vehicle properly and correctly one of them follows training from institutions or driving schools. In this study, the authors helped overcome it by Building a Driving School Information System by analyzing using the Rapid Application Development (RAD) model. Use the Rapid Application Development (RAD) model for software development by minimizing the planning stage and maximizing prototype development. Through this system, prospective drivers can find out all information relating to driving schools, such as training schedules, names of instructors, costs required, types of cars available and comments of prospective drivers who have attended training at the school. This information system is very important for prospective drivers, it is also very useful for the driving school to display all information related to driving learning that will be applied.